Squalus clarkae sp. nov., a new dogfish shark from the Northwest Atlantic and Gulf of Mexico, with comments on the Squalus mitsukurii species complex - Pfleger, Mariah O.; Grubbs, R. Dean; Cotton, Charles F.; Daly-Engel, Toby S. (Zootaxa, 2018)
Sharks of the genus Squalus have slow reproductive rates coupled with low genetic diversity, as is typical of deep-water sharks, making this group slow to rebound from depletion due to overfishing. The number of species within Squalus has been expanding recently due to increased attention on taxonomic revision, and a growing research focus on little-known deep-water sharks in general. Here we use genetics and morphology to describe a new species of dogfish shark, Squalus clarkae sp. nov. from the Gulf of Mexico (GoM) which replaces Squalus mitsukurii in this region, and place it in the context of congeners from the Atlantic and elsewhere. Previously, S. clarkae sp. nov. was considered a part of the Squalus mitsukurii species complex, a group of closely related but distinct species. We sequenced the mitochondrial cytochrome oxidase I and the NADH Dehydrogenase II gene of S. mitsukurii from the type location in Japan, S. clarkae sp. nov. from the GoM, as well as three closely related species (S. cubensis, S. blainville, and S. megalops) and S. cf. mitsukurii from Brazil. Squalus clarkae sp. nov. is genetically distinct from other species with significant statistical support (>98.6% bootstrap support/posterior probability), and 2.8% divergent from S. mitsukurii in the type location of Japan. Morphological estimates also revealed differences between S. clarkae sp. nov., S. mitsukurii, and other Atlantic Squalus species, with S. clarkae sp. nov. exhibiting a longer body, smaller interorbital space, shorter caudal fin, and a differently-proportioned first dorsal fin. In general, dogfish sharks in the Atlantic and GoM are characterized by similar but distinct morphology, significant genetic variation, and small species ranges.